Policy for promoting analytic rigor in intelligence: professionals' views and their psychological correlates. Issue 2 (23rd February 2022) - Mandel, David R.; Hendriks, Tonya L.; Irwin, Daniel
ABSTRACT: Following significant intelligence failures, the United States intelligence community adopted Intelligence Community Directive 203 (ICD203) to promote analytic rigor. We developed two psychometric scales to examine how strongly intelligence professionals ( N = 108) endorsed the analytic standards comprising ICD203 and how strongly they believed their organizations complied with these standards. All ICD203 facets were highly endorsed and clustered into three principal components, and perceived organizational compliance was high. Facets reflecting intelligence aims were endorsed more strongly than those reflecting means. ICD203 endorsement was positively related to conscientious and actively open-minded thinking, whereas perceived organizational compliance was positively correlated with conscientiousness, job satisfaction, and affective and normative commitment.